Novel formyl peptide receptor (FPR) agonists with pyridinone and pyrimidindione scaffolds that are potentially useful for the treatment of rheumatoid arthritis - Crocetti, Letizia (Bioorg Chem, 2020)
The resolution of inflammation is an active response involving the interaction of pro-resolving mediators with specific receptors, such as N-formyl peptide receptor 2 (FPR2). FPRs represent potentially important therapeutic targets for the treatment of some pathologies, including asthma and rheumatoid arthritis. Previously, we identified selective or mixed FPR agonists with a pyridazin-3(2H)-one scaffold, all containing a 4-bromophenylacetamide fragment at N-2. The most effective compounds in this series were EC3, a potent mixed FPR1/FPR2/FPR3 agonist, and EC10, which had a preference for FPR1. We report here a new series of pyridinone and pyrimidindione derivatives containing the 4-(bromophenyl)acetamide substituent that was essential for activity in the pyridazinone series. All new compounds were evaluated for FPR agonist activity in HL60 cells transfected with FPR1 or FPR2 and in human neutrophils. While most of the pyridinone derivatives had reasonable FPR agonist activity in the submicromolar/micromolar range, the pyrimidindione derivatives were less active. Compound 2a (N-(4-bromophenyl)-2-[3-cyano-5-(3-methoxyphenyl)-6-methyl-2-oxopyridin-1(2H)-yl]acetamide) was the most active pyridinone derivative and had a 10-fold preference for FPR2 (EC(50) = 120 nM) versus FPR1 (EC(50) = 1.6 μM). To assess their therapeutic activity, compounds 2a, EC3, and EC10 were evaluated in vivo using a rat model of rheumatoid arthritis. All three compounds increased the pain threshold and reduced pain hypersensitivity in the treated rats versus control rats, although 2a and EC10 were much more effective than EC3. Thus, these FPR agonists represent potential leads to develop for the treatment of inflammatory diseases such as rheumatoid arthritis.